2018
DOI: 10.1016/j.ekir.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 V260E Is a Frequent Cause of Steroid-Resistant Nephrotic Syndrome in Black South African Children

Abstract: IntroductionIn South Africa (SA), steroid-resistant nephrotic syndrome (SRNS) is more frequent in black than in Indian children.MethodsSeeking a genetic basis for this disparity, we enrolled 33 Indian and 31 black children with steroid-sensitive nephrotic syndrome (SSNS) and SRNS from KwaZulu-Natal, SA; SRNS children underwent kidney biopsy. We sequenced NPHS2 and genotyped APOL1 in 15 SSNS and 64 SRNS unrelated patients and 104 controls and replicated results in 18 black patients with steroid-resistant focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…As expected (Eddy & Symons, 2003), the children with SRNS were significantly older at presentation, otherwise the groups were demographically similar. Genetics are known to play a role in steroid-responsiveness (Adeyemo et al, 2018;Asharam et al, 2018;Govender et al, 2019;Gribouval et al, 2018Gribouval et al, , 2019. However, while genetic and other mechanisms underlying steroid-responsiveness in this small cohort were not evaluated in the present study, they have been the subject of previously reported biomarker studies (Agrawal et al, 2020;Gooding et al, 2020).…”
Section: Hypercoagulopathy Improves In Children With Steroid-sensitmentioning
confidence: 83%
“…As expected (Eddy & Symons, 2003), the children with SRNS were significantly older at presentation, otherwise the groups were demographically similar. Genetics are known to play a role in steroid-responsiveness (Adeyemo et al, 2018;Asharam et al, 2018;Govender et al, 2019;Gribouval et al, 2018Gribouval et al, , 2019. However, while genetic and other mechanisms underlying steroid-responsiveness in this small cohort were not evaluated in the present study, they have been the subject of previously reported biomarker studies (Agrawal et al, 2020;Gooding et al, 2020).…”
Section: Hypercoagulopathy Improves In Children With Steroid-sensitmentioning
confidence: 83%
“…All those with NPHS2 260E/E mutation were unresponsive to therapy. The authors concluded that genotyping V260E in Black children from South Africa with NS would identify a sizable proportion of Black children with steroid-resistant FSGS, potentially sparing these children the use of steroids and other immunosuppressive agents as well as the need to undergo kidney biopsy, which is an invasive procedure 54 …”
Section: Literature Search Strategies and Data Collectionmentioning
confidence: 99%
“…In South Africa, there are limited genetic studies on kidney disease, including FSGS, among children. Asharam et al (2018) 20 reported on 33 Indian and 31 black children from Kwa-Zulu Natal with SSNS and SRNS. In their study, APOL1 variants were not associated with NS, but the NPHS2 V260E allele was specifically associated with SRNS (with FSGS) in black children; 8 were homozygous for the variant (OR 21; 95% CI, 2.8–960) and no heterozygotes were observed.…”
Section: Introductionmentioning
confidence: 99%